2016
DOI: 10.1159/000442666
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Segmental Vitiligo in Children with the Combination of 1-mm Minigrafts and Phototherapy

Abstract: Background: Minigrafts using a 1-mm biopsy punch (1-mm minigrafts) are being increasingly used to treat vitiligo. However, there have been few reports of the use of 1-mm minigrafts in pediatric patients. Objective: To examine the effectiveness of combination therapy with 1-mm minigrafts and phototherapy in children with segmental vitiligo. Methods: Minigrafts were placed in 13 patients aged ≤16 years with segmental vitiligo. Following surgery, 11 patients underwent irradiation with excimer laser light and 2 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 16 publications
(24 reference statements)
0
15
0
1
Order By: Relevance
“…Whitening of hairs (leukotrichia or poliosis) is more commonly observed with SV and can be a marker of poor response to treatment. To date, pathogenesis of SV is not entirely well‐known; however, previous studies showed increased blood flow and vasodilatation in depigmented skin of SV due to impaired sympathetic response results from increased α 2 and β adrenergic receptors and nitric oxide syntheses 7–37 . Other mechanisms such as increased levels of pro‐inflammatory cytokines, cytotoxic effects of neuropeptides on melanocytes, and destruction of melanocytes secondary to oxidative stress, and CD8 cytotoxic T lymphocytes have been proposed in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Whitening of hairs (leukotrichia or poliosis) is more commonly observed with SV and can be a marker of poor response to treatment. To date, pathogenesis of SV is not entirely well‐known; however, previous studies showed increased blood flow and vasodilatation in depigmented skin of SV due to impaired sympathetic response results from increased α 2 and β adrenergic receptors and nitric oxide syntheses 7–37 . Other mechanisms such as increased levels of pro‐inflammatory cytokines, cytotoxic effects of neuropeptides on melanocytes, and destruction of melanocytes secondary to oxidative stress, and CD8 cytotoxic T lymphocytes have been proposed in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several combination therapies have been introduced to obtain better results and to reduce risks. 2 The prolonged duration of therapy is the main reason for patient noncompliance. 3 Platelet-rich plasma (PRP) is composed of high concentration of platelets with high concentration of growth factors (GFs).…”
Section: Introductionmentioning
confidence: 99%
“…. From these 39 studies, seven studies compared one phototherapy with another or with no phototherapy as an addition to the surgical treatment in vitiligo; these studies were marked as ‘comparative’ . Furthermore, in the other 32 studies, the results of only one phototherapy were presented; these studies were marked as ‘non‐comparative’ .…”
Section: Resultsmentioning
confidence: 99%